THE RELATIONSHIP BETWEEN LOCUS OF EXTERNAL CONTROL AND CYBERLOAFING: THE ROLE OF ACADEMIC SELF-EFFICACY MEDIATION IN COLLEGE STUDENTS - Diah Charasati; Zakki Nurul Amin (Jurnal Konseling Pendidikan Islam, 2025)
The advancement of digital technology has increased the opportunities for university students to engage in cyberloafing, which refers to the use of the internet for non-academic activities during lectures. This study aims to analyze the relationship between external locus of control and cyberloafing behavior by examining the mediating role of academic self-efficacy. Using a correlational research design, data were collected from 345 students who completed scales measuring external locus of control, academic self-efficacy, and cyberloafing. Data were analyzed through bootstrapping techniques (N = 5000) using Hayes' PROCESS Model 4. The results indicate that external locus of control has a significant negative effect on cyberloafing (β = -0.36). However, academic self-efficacy partially mediates this relationship by exerting a positive indirect effect (β = 0.10). These findings suggest that although academic self-efficacy generally has beneficial effects, in certain contexts it may foster overconfidence that actually increases the tendency to engage in cyberloafing. This study highlights the importance of strengthening academic self-efficacy alongside self-control training to reduce deviant behaviors within digital learning environments.